ANALISIS PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG (PERPPU) SEBAGAI OBJEK PENGUJIAN DI MAHKAMAH KONSTITUSI - Fitriyani, Nia; Haryono, Dodi; Rauf, Muhammad A. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The authority of the Constitutional Court in the 1945 Constitution of the Republic ofIndonesia (1945 Constitution of the Republic of Indonesia) after the issuance of MK DecisionNumber 138/PUU-VIII/2009. The Constitutional Court stated its authority to review GovernmentRegulations in Lieu of Law (Perppu) against the Constitution, relying on the interpretation thatPerppu is in a position parallel to the Law, in accordance with Law Number 12 of 2011concerning the Formation of Legislative Regulations . MethodThis research uses a type of normative legal research (normative law research) usingnormative case studies in the form of legal products produced, reviewing statutory regulations,books and journals related to this research, as well as analyzing Constitutional Court DecisionNumber 138/PUU- VIII/2009.The results of this research explain that the Constitutional Court has the authority toreview Perppu and regulations that are lower in level than the 1945 NRI Constitution whichpositions Perppu in the same position as the Law by using a slash (/), cannot change the contentsof the Constitution NRI of 1945, which clearly differentiates between Laws and PerppuKeywords: Authority, Constitutional Court, Testing